Haploidentical CD3+ TCR αβ/CD19+-depleted HSCT for MHC class II deficiency and persistent SARS-CoV-2 pneumonitis - Flinn, Aisling (My University, 2023)
Background: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection leads to coronavirus disease 2019 (COVID-19), which can range from a mild illness to a severe phenotype characterized by acute respiratory distress needing mechanical ventilation. Children with combined immunodeficiencies might be unable to mount a sufficient cellular and humoral immune response against COVID-19 and have persistent disease. Objective: Our aim was to describe a child with combined immunodeficiency and a favorable post-hematopoietic stem cell transplant (HSCT) course following a haploidentical HSCT in the presence of persistent SARS-CoV-2 infection. Methods: A 13-month-old girl with MHC class II deficiency developed persistent pre-HSCT SARS-CoV-2 infection. Faced with a significant challenge of balancing the risk of progressive infection due to an incompetent immune system with the danger of inflammatory pneumonitis peri-immune reconstitution after HSCT, the patient's physicians performed a maternal (with a recent history of COVID-19 infection) haploidentical HSCT. The patient received regdanvimab (after stem cell infusion) and remdesivir (before and after stem cell infusion). Results: The patient exhibited a gradual increase in her cycle threshold values, implying a reduction in viral RNA with concomitant expansion in the CD3 lymphocyte subset and clinical and radiologic improvement. Conclusions: Combination of adoptive transfer of maternal CD45RO+ memory addback T lymphocytes after haploidentical HSCT and use of regdanvimab (a SARS-CoV-2-neutralizing mAb) and remdesivir may have led to the successful outcome in our patient with severe immunodeficiency after she had undergone HSCT. This case highlights the role of novel antiviral strategies (mAbs and CD45RO+ memory T lymphocytes) in contributing to viral clearance in a challenging clinical scenario.
PUBLISHED
Keywords: CD3+ TCR αβ/CD19+–depleted haploidentical transplant; COVID-19; COVID-19, Coronavirus disease 2019; HSCT, Hematopoietic stem cell transplant; IEI, Inborn error of immunity; MHC class II deficiency; RFXANK, Regulatory factor X associated ankyrin containing protein; SARS-CoV-2; SARS-CoV-2, Severe acute respiratory syndrome coronavirus 2; TCR, T cell receptor; regdanvimab.; Immunology, Inflammation & Infection; Immune system; Immunology, Immunotherapy; PAEDIATRICS